2023
DOI: 10.2147/ppa.s390409
|View full text |Cite
|
Sign up to set email alerts
|

Perspective and Experience of Patients with Aplastic Anemia on Medication Adherence

Hangting Li,
Xiaolian Wu,
Jiaoni Shen
et al.

Abstract: Background Drug treatment is critical for patients with aplastic anemia, and medication adherence directly impacts the therapeutic effect. Poor medication adherence is common among patients with chronic diseases. However, knowledge of the perceptions and experiences of patients with aplastic anemia regarding taking prescribed medicines is limited. Objective To gain insights into the perceptions and experiences of patients with aplastic anemia regarding taking prescribed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“… 12 The findings of a qualitative analysis, focusing on the content of online communication among individuals with rosacea, revealed that proactive health education encompassing topics such as etiology, treatment, diet, and skincare exhibited a positive impact. This educational approach effectively reduced patient confusion regarding the disease, patient’s adherence to the medications and fostered a positive doctor-patient relationship 13 , 14 . The objective of this study was to conduct a retrospective analysis of the factors that impact the treatment of rosacea patients who engage in regular follow-up through self-management support within the framework of the new media chronic disease management model.…”
Section: Introductionmentioning
confidence: 99%
“… 12 The findings of a qualitative analysis, focusing on the content of online communication among individuals with rosacea, revealed that proactive health education encompassing topics such as etiology, treatment, diet, and skincare exhibited a positive impact. This educational approach effectively reduced patient confusion regarding the disease, patient’s adherence to the medications and fostered a positive doctor-patient relationship 13 , 14 . The objective of this study was to conduct a retrospective analysis of the factors that impact the treatment of rosacea patients who engage in regular follow-up through self-management support within the framework of the new media chronic disease management model.…”
Section: Introductionmentioning
confidence: 99%